Increasing and Decreasing Perceived Bias by Distorting the Quality of News Website Design - Spillane, Brendan; Wade, Vincent; Lawless, Séamus (BCS Learning & Development Ltd, 2018)
News website design has previously been shown to impact perceived credibility, and one of its core dimensions and measures, bias. This paper demonstrates that by adapting the quality of the visual presentation of webpages from nine of the most popular news websites, to reflect high quality and low quality news agencies, we can predicatively increase or decrease perceived bias in the news articles they contain. This effect was common across the websites of traditional print, news magazine, and international news agencies, and across articles with different levels of bias. The distortions focused on the visual quality of a websites’ design, including the amount, size, and prominence of advertising, news article meta data, supporting material, gaudy calls to action, and the percentage of the webpage dedicated to the news article. Higher quality visual experiences reflecting quality news agencies were shown to reduce bias, while those with a low quality visual experience reflecting less professional news agencies increased bias. Significant differences were also found between low and high quality designs showing the same news articles. This paper reports results on one part of a large study on the impact of visual appearance and design on the perception of bias in online news.
Proceedings of the 32nd British HCI Group Annual Conference on People and Computers:
British HCI 2018
Keywords: Bias; Credibility; News website design; Personalization; Digital Engagement; Telecommunications; BIAS; Internet News; NEWSPAPER BIAS; News; News Website Design; Online News; Communication